(untitled) (Journal of The Colloquium for Information Systems Security Education, 2023)
This paper presents an experience report on using an interactive program visualization tool — Dynamic, Interactive Stack-Smashing Attack Visualization (DISSAV) — and a complementary active-learning exercise to teach stack smashing, a key software security attack. The visualization tool and active-learning exercise work synergistically to guide the student through challenging, abstract concepts in the advanced cybersecurity area. DISSAV and the exercise are deployed within the software security module of an undergraduate cybersecurity course that introduces a broad range of security topics. A study is designed that collects and evaluates student perceptions on the user interface of DISSAV and the effectiveness of the two resources in improving student learning and engagement. The study finds that over 80% of responses to user interface questions, 66% of responses to student learning questions and 64% of responses to student engagement questions are positive, suggesting that the resources improve student learning and engagement in general. The study does not find discernible patterns of difference in responses from students of different ages and varying levels of prior experience with stack smashing attacks, program visualization tools and C programming.